Analisis Dampak Cfw Program Kotaku Dalam Pemberdayaan Perekonomian Masyarakat Ditengah Pandemi Covid-19 Ditinjau Dari Perspektif Ekonomi Islam (Studi Kasus Kelurahan Sepang Jaya Labuhan Ratu Kota Bandar Lampung) - Rachmawati, Della (Sharia Journal and Education Center Publishing, 2024)
Abstract The Covid-19 pandemic has caused many companies to close operations and lay off employees. As a solution, the Ministry of Public Works and Public Housing through the Directorate General of Human Settlements adopted a cash for work mechanism in the KOTAKU government assistance program (BPM). This research discusses the impact of the KOTAKU program on community empowerment and the economy amid the Covid-19 pandemic and the Islamic economic perspective on this impact. The research method used is qualitative and a case study on the KOTAKU program in Sepang Jaya Village, Bandar Lampung City. Primary data is obtained from in-depth interviews, focus group discussions, observations or surveys, while secondary data comes from documentation and literature studies related to the KOTAKU program. The results showed that the KOTAKU program had a positive impact on the community of Sepang Jaya Village. The program creates jobs, increases income, and meets household needs. The success of this program is supported by cooperation between the community and the local government. This positive impact is in accordance with Islamic teachings, helping to overcome unemployment and poverty due to the Covid-19 pandemic, as well as increasing togetherness and social responsibility. Keywords: CFW KOTAKU, Empowerment, Economy Abstrak Pandemi Covid-19 menyebabkan banyak perusahaan menutup operasional dan merumahkan karyawan. Sebagai solusi, Kementerian Pekerjaan Umum dan Perumahan Rakyat melalui Direktorat Jenderal Cipta Karya mengadopsi mekanisme cash for work dalam program bantuan pemerintah untuk masyarakat (BPM) KOTAKU. Penelitian ini membahas dampak program KOTAKU terhadap pemberdayaan dan perekonomian masyarakat di tengah pandemi Covid-19 serta perspektif ekonomi Islam terhadap dampak tersebut. Metode penelitian yang digunakan adalah kualitatif dan studi kasus pada program KOTAKU di Kelurahan Sepang Jaya, Kota Bandar Lampung. Data primer diperoleh dari in-depth interview, focus group discution, observasi atau survei, sedangkan data sekunder berasal dari dokumentasi dan studi pustaka terkait program KOTAKU. Hasil penelitian menunjukkan bahwa program KOTAKU memberikan dampak positif bagi masyarakat Kelurahan Sepang Jaya. Program ini menciptakan lapangan kerja, meningkatkan pendapatan, dan memenuhi kebutuhan rumah tangga. Keberhasilan program ini didukung oleh kerjasama antara masyarakat dan pemerintah setempat. Dampak positif ini sesuai dengan ajaran Islam, membantu mengatasi pengangguran dan kemiskinan akibat pandemi Covid-19, serta meningkatkan kebersamaan dan tanggung jawab sosial. Kata Kunci: CFW KOTAKU, Pemberdayaan, Perekonomian